Application of magneto-rheological damper for car suspension control - Rashid, Muhammad Mahbubur; M.A, Hussain; N.Abd, Rahim (Asian Network for Scientific Information, 2006)
The MR damper is a control device that consists of a hydraulic cylinder filled with magnetically polarizable particles suspended in a liquid. MR dampers dissipate vibration by absorbing energy. Magnetorheological (MR) fluids dampers are very effective to control vibration, which use MR fluids to produce controllable damping force and provide both the reliability of passive systems and the facility of active control systems with small power supply. Due to their mechanical simplicity, high dynamic range, low power requirements